STUDY OF MITIGATION ON THE ROAD NETWORK IN AREAS PRONE TO EARTHQUAKE AND TSUNAMI DISASTER (THE APPLICATION OF GIS ON A CASE STUDY OF COASTAL REGIONS OF TASIKMALAYA AND PANGANDARAN) - LAKSANA, NOEGRAHA
The purpose of this study is to conduct a study on mitigation of risk analysis based on road network in areas prone to earthquake and tsunami disaster, approach potential insecurity tsunami measurement results obtained based on the data runoff and inundation length by Centre of Geological Survey for coastal regions of Tasikmalaya and by Agency For The Assessment And Application Of Technology (BPPT) with Institute Geological and Nuclear Science-New Zealand (GNS) for coastal regions of Pangandaran, then GIS analysis undertaken to determine the potential distribution area and level of flowdepth on a roads through Flowdepth simulation so retrieved a list of roads that are at risk of a tsunami wave. Simulation results serve as computational data that will be used in determining the risk rating of the roads affected by the tsunami by using the method of Analytical Hierarchy Process (AHP). The process of solving method of AHP is rank calculated weights and indicators matrix ranking factors its criteria, The final results of the ranking value used as indicators to classify the level of risk roads with three ranks of tsunami risk, i.e. high, medium, and low. Based on the results analysis of the 16 roads which had risky affected to the coastal tsunami inundation in Tasikmalaya regency, 7 roads categories as high risk road sections, 6 roads in to medium risk, and 3 roads into low risk, for Pangandaran coastal regency, the 17 roads which had risky affected to the coastal tsunami inundation 6 roads categories as high risk road sections, 10 roads in to medium risk, and 1 roads into low risk The end result in this study is preparation of mitigation effort in field of road in the form of structural and non-structural mitigation. Structural mitigation efforts include road widening for evacuation routes, widening the sidewalks for pedestrians, improvements and upgrading of road pavement and improvements village road which used as evacuation routes. meanwhile for non structural mitigation efforts is preparation of evacuation zone map and evacuation routes in every region of the coastal district of Tasikmalaya and Pangandaran Regency